Pengaruh Good Governance Terhadap Kinerja Pemerintah Daerah Dengan Sistem Pengendalian Internal Sebagai Variabel Moderasi - Novita Sari; Agus Kurniawan; Nurhayati Nurhayati (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The effort to implement good governance reflects the government's desire to apply good governance in the administration of regional government. A good government SPI can also influence the actions and activities carried out continuously by the leadership and all staff to provide adequate assurance of the achievement of organizational goals. This research was conducted to determine the effect of good governance on the performance of local government, to determine the effect of the internal control system on the performance of local government, to determine whether the internal control system moderates the effect of good governance on the performance of local government and to understand the Islamic Economic perspective on the effect of good governance on the performance of local government in the Department of Industry and Trade of Lampung Province. The method used employs a quantitative approach. The population in this study consists of all employees of the Department of Industry and Trade of Lampung Province, and the sample taken was 46 respondents using the purposive sampling technique. In this study, it is shown that poor governance will not affect the performance of the regional government at the Department of Industry and Trade of Lampung Province. But the higher the internal control system in the Department of Industry and Trade of Lampung Province, the more it will be able to improve the performance of the regional government, and the higher the internal control system in the Department of Industry and Trade of Lampung Province, the more it will strengthen the influence of good governance on the performance of the regional government.